Performance experiment of ultra high temperature cementing slurry system - Zou, Qiang; Chen, Xu; Zhong, Shiming; Yi, Dan; Liu, Liankai (Frontiers in Materials, 2024)
The expanding reach of oil and gas exploration in China, delving into deep and ultra-deep wells, the formation temperature is getting higher and higher, posing heightened demands on the temperature resistance of cement slurry. This presents significant challenges to drilling and completion operations. To address this issue, this study focuses on the performance requirements of cement slurry in ultra-high temperature cementing operations. By formulating an ultra-high temperature conventional density cement slurry with high-temperature resistant additives like DRF-1S and DRH-2L, the research establishes an indoor testing framework. Evaluation encompasses settlement stability, water loss performance, thickening characteristics, and mechanical properties. Results indicate that optimal silica sand dosage is 50%, and the conventional density cement slurry system, featuring DRF-1S and DRH-2L, meets cementing needs in temperatures ranging from 180 to 210 ℃, achieving a breakthrough in high-temperature resistance. Controlling API water loss within 100mL, adjusting thickening time, and ensuring settlement stability below 0.04g/cm3, this system, along with the anti-decay material DRB-3S, guarantees a 28-day compressive strength exceeding 50MPa at 210 ℃. The research results provide a basis for the application of UHTE cementing technology, and facilitate the subsequent application to test the effect of the new additive, and develop a better UHTE cementing cement additive.